SEARCH ENGINE OPTIMIZATION EFFECT OF TRAFFIC DENSITY ON THE NUMBER OF VISITORS AT THE WEBSITE. - Tri Indah Astuti (Jurnal Sistem Informasi, 2010)
Internet is the medium of the most in expensive, effective and fast in conveyinformation. Other media such as brochures for example have to do print and sendactivity is physically so it will require a long time to delivery. Television media isvery expensive, and only Just a few seconds can be displayed.With internet we just to pay for the internet provider, create website andupdating contents. Although it does'nt mean anything if the website are not visited bypeople. Effort is needed to the website can be visited by many people. The mosteffective way to bring visitors on the website is through Search Engine Optimization,or better known as SEO.Search Engine Optimization is a technique that Optimize website createdeasily found or indexed by search engines such as Google, etc. With these techniqueswill make the website are the results Google search that will certainly make it easierfor other people can access website and automatically beneficial for them.For the implementation can be tested directly on the website follow someguidelines for search engines, especially Google. With the Search EngineOptimization is expected that the site owners or a website can increase the number ofvisitors the website and at once introduce and increase its revenue with the website